Agrobacterium-mediated transformation of Hevea cells derived from in vitro and in vivo seedling cultures - Arokiaraj, P. (2013)
Tumour tissue was produced on stems of in vitro and in vivo propagated rubber (Hevea brasiliensis) seedlings of PB 5/51, infected with a strain of Agrobacterium tumefaciens 541 (isolated by the Rubber Research Institute of Malaysia in 1971). The tumour tissues exhibited phytohormone-independent growth in tissue culture and produced octopine. In contrast, controls inoculated with distilled water on seedlings did not produce crown gall. Octopine-utilising Agrobacterium strain 541 was distinguished from non-utilisers on a solid medium containing octopine as the only added nitrogen source with bromothymolblue (BTB) as the pH indicator. On blue BTB plates, this strain formed orange-yellow colonies, while those formed by non-utilisers were translucent. This process of cell transformation may facilitate the transfer of genes of economic importance to rubber.